(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article discusses the role of learning materials in the learning process and their impact on effectiveness. The article is aimed at studying the processes of adoption and adaptation of educational materials. It is important to adapt educational materials to the age, characteristics, and learning styles of students. The article also highlights the advantages of providing educational materials in interactive and digital formats.